Pengembangan Buku Ajar Berbasis Quantum Teaching Berbantuan Augmented Reality Materi Keberagaman sebagai Identitas Nasional Bangsa Indonesia - Sekarsari, Peni; Sukriono, Didik; Dayati, Umi (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2023)
This study aimed to develop and test the feasibility, attractiveness, and effectiveness of textbooks based on quantum teaching with the help of augmented reality material on Diversity as the National Identity of the Indonesian Nation. The procedure used was research and development based on the steps proposed by Borg and Gall. The product produced in this development study is a quantum teaching-based textbook assisted by augmented reality on Diversity as the National Identity of the Indonesian Nation, which is appropriate, attractive, and effective. The product feasibility test is based on the validation results of material experts by 83.7 percent, media expert validation by 92.9 percent, and learning expert validation by 89.4 percent. The product attractiveness test was based on the results of the small group trial of 85.9 percent and the results of the large group trial of 87.1 percent. The product effectiveness test was based on the results of the large group trials: the average pretest value of 64.9 and the post-test of 84.1. It shows an increase in the average value obtained by students, equal to 19.2.